PENINGKATAN MINAT LITERASI AKUNTANSI DAN KEUANGAN PADA SISWA LPK SAKURA EDUCATION - Laily Ramadhani; Siswanto; Marliyoni Halawa (LPPM Amik Widya Loka, 2025)
This Community Service activity aims to introduce financial literacy programs for students. Literacy education is important for students so that they are accustomed to managing finances well in the future. In Indonesia, financial literacy education is still very rare, both in the family and school environment, the provision of education about financial literacy has not been carried out seriously and planned. This service is expected to be useful for simple financial management knowledge for early childhood through the